(untitled) (Guruku: Jurnal Pendidikan Profesi Guru, 2025)
Multicultural education plays a crucial role in facing the challenges of cultural, religious and ethnic diversity in society. This article aims to analyse the role of teachers in integrating multicultural education into the primary school curriculum, focusing on implementation strategies and challenges faced. This research uses a qualitative approach through the literature study method, by collecting and analysing data from various academic sources such as education, psychology and multiculturalism journals. The results showed that teachers act as facilitators, social change agents, and intercultural liaisons, who are able to increase students' cross-cultural awareness, empathy, and collaboration skills. Some of the effective strategies identified include the preparation of cultural context-based teaching materials, open discussions, and collaboration with parents and communities. However, challenges such as lack of teacher training, resources and policy support still need to be addressed. This article emphasises the importance of collaboration between teachers, schools and communities to create inclusive learning environments while preparing students to become tolerant and competitive global citizens.